2008
DOI: 10.1088/0957-4484/19/34/345102
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between carbon nanotubes and mammalian cells: characterization by flow cytometry and application

Abstract: We show herein that CNT-cell complexes are formed in the presence of a magnetic field. The complexes were analyzed by flow cytometry as a quantitative method for monitoring the physical interactions between CNTs and cells. We observed an increase in side scattering signals, where the amplitude was proportional to the amount of CNTs that are associated with cells. Even after the formation of CNT-cell complexes, cell viability was not significantly decreased. The association between CNTs and cells was strong eno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
101
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 31 publications
2
101
0
1
Order By: Relevance
“…Most importantly, f -CNT have the ability to interact with biological components and be internalized efficiently in different cell types by different mechanisms (20)(21)(22). Several studies have shown promising results, exploiting f -CNT characteristics for pDNA and siRNA delivery in vitro and in vivo (17,18,20,(23)(24)(25)(26)(27)(28). Chemically functionalized single-walled CNT have been able to deliver siRNA to knockdown the expression of telomerase reverse transcriptase in an Lewis Lung Carcinoma mouse tumor model (26).…”
mentioning
confidence: 99%
“…Most importantly, f -CNT have the ability to interact with biological components and be internalized efficiently in different cell types by different mechanisms (20)(21)(22). Several studies have shown promising results, exploiting f -CNT characteristics for pDNA and siRNA delivery in vitro and in vivo (17,18,20,(23)(24)(25)(26)(27)(28). Chemically functionalized single-walled CNT have been able to deliver siRNA to knockdown the expression of telomerase reverse transcriptase in an Lewis Lung Carcinoma mouse tumor model (26).…”
mentioning
confidence: 99%
“…Hence, flow cytometry is a powerful tool for investigating the interaction between nanoparticles and cells. 32 The effect of zinc oxide nanoparticles on plasma membrane damage was assessed by permeability to propidium iodide. Cells were incubated with 20 µg/mL of zinc oxide nanoparticles for 6 hours (corresponding to an intracellular zinc concentration of 0.5 mM).…”
mentioning
confidence: 99%
“…The strong interaction between osteocytes and the nanoparticles is reflected by the parallel strong increase of side scatter compared with the control cultures, indicative of increased cellular complexity due to nanoparticle-cell interaction. 32 It has been reported that nanomaterials can promote autophagy, [33][34][35][36] and this could be an alternative biological process altering the side scatter profile. Because autophagy ultimately causes cell death, the negligible cytotoxicity induced by zinc oxide nanoparticles on osteocytes (Figure 8) suggests that the alteration in side scatter could be a result of interaction with the nanomaterials rather than an autophagic process.…”
mentioning
confidence: 99%
“…Magnetized carbon nanotubes (MCNTs) driven by a magnetic force spear into cells and deliver molecular payloads. This method has demonstrated remarkable biocompatibility regarding cell viability, cell growth, cell cycle, DNA synthesis, cellular stimulation, and Akt and MAP kinase activities (25,26). Given that the nanotube can enter cells without detectable perturbations, using it to extract molecules from live cells would be an appealing mode of exploration.…”
Section: Resultsmentioning
confidence: 99%